2014
DOI: 10.1103/physreve.90.022802
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic networks are almost nonfractal: A comprehensive evaluation

Abstract: Network self-similarity or fractality are widely accepted as an important topological property of metabolic networks; however, recent studies cast doubt on the reality of self-similarity in the networks. Therefore, we perform a comprehensive evaluation of metabolic network fractality using a box-covering method with an earlier version and the latest version of metabolic networks, and demonstrate that the latest metabolic networks are almost self-dissimilar, while the earlier ones are fractal, as reported in a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…Additionally, the fractal and self-similar properties are widely applied in biological systems, including development of the algorithm to count the motifs in the biological networks [265], prediction of essential genes [305], and measuring the importance of proteins [306]. However, different from the previous view [288] in which metabolic networks exhibit self-similarity (fractality) using a box-counting method, Takemoto [307] found that metabolic networks are almost non-fractal for the increase in network density of the latest metabolic network data, highlighting the needs for a more suitable definition and careful examination of network fractal and self-similarity properties.…”
Section: Fractal and Self-similaritymentioning
confidence: 99%
“…Additionally, the fractal and self-similar properties are widely applied in biological systems, including development of the algorithm to count the motifs in the biological networks [265], prediction of essential genes [305], and measuring the importance of proteins [306]. However, different from the previous view [288] in which metabolic networks exhibit self-similarity (fractality) using a box-counting method, Takemoto [307] found that metabolic networks are almost non-fractal for the increase in network density of the latest metabolic network data, highlighting the needs for a more suitable definition and careful examination of network fractal and self-similarity properties.…”
Section: Fractal and Self-similaritymentioning
confidence: 99%
“…After computing b( ) for a network, we want to decide whether the network is fractal or not. A typical indicator of a non-fractal network is an exponential form: b( ) ∝ exp(c ), where c is a constant factor [29]. Therefore, comparison of the fitting of the obtained b( ) to power-law and exponential functions enables us to determine the fractality of the network.…”
Section: ) Graph Fractalitymentioning
confidence: 99%
“…Otherwise, it was supposed to be non-fractal. This procedure of fitting and comparison follows that used in [29].…”
Section: A Setupmentioning
confidence: 99%
“…Regardless of the layout, metabolic networks typically contain many poorly connected nodes interconnected by a few heavily connected nodes (the hubs), the latter being especially associated with cofactors such as ATP, NADH, glutamate and coenzyme A [29] . Consequently, the node connectivity, defined as the number of edges per node, shows a heavy-tailed probability distribution [30] , [31] , [32] , [33] , [34] , [35] , [36] . Furthermore, metabolic networks have a non-random topology and are likely organized in a hierarchical modular structure ( Fig.…”
Section: Introductionmentioning
confidence: 99%